Usаgе оf stаtistics in studеnt rеsеаrch wоrk (Herald of Journalism, 2020)
The relevance of the topic is due to the demand for statistical processing of experimental data in the preparation of research work. Students often have difficulty analyzing a large amount of data. However in order to analyze the data for practical purposes, it is not necessary to be fluent in mathematical formulas, probability theory, or mathematical analysis. There are various types of programs that can be utilized without in-depth knowledge of the applied mathematics.The purpose of the article is to present methods of statistical processing of information, the main directions of the use of data in student research papers. The authors of the article introduce the types of research in the field of statistics, give examples for each of them. They consider where the data comes from, how they receive the data, what they look for in the data, how to process the data, and how best to work with the results. The main direction of scientific research is a description of skills, the process of building a model, the applied software and algorithmic tools, the possibility of using various statistical data processing programs.The research methodology is based on the concepts of domestic and foreign researchers, who have a scientific platform, based on the principles of objectivity, concreteness. The value of this work is that students will learn to use these statistical methods in their research, develop a research methodology, process and interpret data, and correctly use the results.
Keywords: statistical method, data processing, statistical research; student studies; statistical data processing.